A Deeper Union: From a Failed Project to the European Quality Lead - Karl Aiginger (Intereconomics, 2021)
After President Trump's departure, many expected that the transatlantic partnership would return to its previous state with the US playing a leading role. This article challenges that view. Instead, a new world order is foreseen, with different partnerships and spheres of influence. Europe can decide whether it wants to remain small and homogeneous or a larger but also more heterogenous Union that leads in welfare indicators such as life expectancy, fighting poverty and limiting climate change. Expanding this lead and communicating its uniqueness can empower Europe to combine enlargement and deepening, which appears unlikely without changes in governance and self-confidence.
Keywords: 330